2022
DOI: 10.1093/neuonc/noac087
|View full text |Cite
|
Sign up to set email alerts
|

Entrectinib in children and young adults with solid or primary CNS tumors harboring NTRK, ROS1, or ALK aberrations (STARTRK-NG)

Abstract: Background Entrectinib is a TRKA/B/C, ROS1, ALK tyrosine kinase inhibitor approved for treatment of adults and children aged ≥12 years with NTRK fusion-positive solid tumors and adults with ROS1 fusion-positive non-small cell lung cancer. We report analysis of the STARTRK-NG trial, investigating the recommended phase 2 dose (RP2D) and activity of entrectinib in pediatric patients with solid tumors including primary central nervous system tumors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 31 publications
2
48
0
8
Order By: Relevance
“…Its use in pediatric hematological cancers is still discussed, regardless of its tumor-agnostic action. The STARTRK-NG phase I/II study on pediatric patients (none with NHL) treated with entrectinib for locally advanced or metastatic solid tumors or primary CNS tumors and/or who had no satisfactory treatment options, revealed no increased risk of infection (grade ≥3 infections, neutropenia, and lymphopenia in 2.3%, 7%, and 2.3%, respectively; mainly lung and urinary tract infections; significantly more device-related infections than in adults) [ 13 , 147 ]. Logistic regression models indicated that the probability of a patient experiencing a grade ≥3 treatment-related or a serious adverse event increased with entrectinib exposure > 600 mg/day [ 148 ].…”
Section: Tyrosine Kinase Inhibitors (Tkis)mentioning
confidence: 99%
“…Its use in pediatric hematological cancers is still discussed, regardless of its tumor-agnostic action. The STARTRK-NG phase I/II study on pediatric patients (none with NHL) treated with entrectinib for locally advanced or metastatic solid tumors or primary CNS tumors and/or who had no satisfactory treatment options, revealed no increased risk of infection (grade ≥3 infections, neutropenia, and lymphopenia in 2.3%, 7%, and 2.3%, respectively; mainly lung and urinary tract infections; significantly more device-related infections than in adults) [ 13 , 147 ]. Logistic regression models indicated that the probability of a patient experiencing a grade ≥3 treatment-related or a serious adverse event increased with entrectinib exposure > 600 mg/day [ 148 ].…”
Section: Tyrosine Kinase Inhibitors (Tkis)mentioning
confidence: 99%
“…Entrectinib is a potent multikinase inhibitor with systemic inhibition activity against multiple oncogenic kinases, such as neurotrophic tyrosine receptor kinase (NTRK), anaplastic lymphoma kinase (ALK) and proto-oncogene tyrosine protein kinase ROS1 (ROS1; Desai et al, 2022 ). Compared with similar drugs like larotrectinib and crizotinib, the designment of entrectinib facilitates it easily to penetrate the blood–brain barrier for the chemotherapy of tumors in the central nervous system (CNS; Doebele et al, 2020 ; Drilon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ceritinib, a second-generation ALK inhibitor, also benefit patients with ROS1-positive NSCLC [108]. In 2019, entrectinib that targets ROS1 and ALK was approved for adults with metastatic ROS1-positive NSCLC [109]. Entrectinib can pass through the blood-brain barrier and is clinically proven effective against primary and metastatic brain diseases [110].…”
Section: Ros1 Fusions/rearrangementsmentioning
confidence: 99%